2021
DOI: 10.3390/s21217062
|View full text |Cite
|
Sign up to set email alerts
|

Model Test Study on Deformation of Snowflake Shaped Steel Sheet Pile Based on OFDR

Abstract: As a newly developed pile foundation, the snowflake shaped steel sheet pile is composed of three Y-shaped sections with an included angle of 120° and has a large specific surface area, which can give full play to the side friction of pile and improve the bearing capacity of single pile. At the same time, the snowflake shaped steel sheet pile has a high strength, relatively few materials, and it has good prospects with engineering applications. In order to accurately grasp the mechanical characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results showed that geogrids can provide resistance in the active zone under strip footing surcharge loading. Gao et al [22] developed a snowflake-shaped steel sheet pile and conducted model tests based on optical frequency-domain reflector distributed optical fiber sensor technology. The results indicated that due to the complex cross-section shape, strain varies with position.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that geogrids can provide resistance in the active zone under strip footing surcharge loading. Gao et al [22] developed a snowflake-shaped steel sheet pile and conducted model tests based on optical frequency-domain reflector distributed optical fiber sensor technology. The results indicated that due to the complex cross-section shape, strain varies with position.…”
Section: Introductionmentioning
confidence: 99%
“…Steel sheet piles were used as pile foundations with a large surface area and high strength to improve the bearing capacity. Model tests were conducted using the OFDR technique, and the results showed its strain distribution characteristics [14]. The effect of the surface roughness of steel sheet piles on the lateral bearing behavior of piles embedded in the sand was investigated.…”
Section: Introductionmentioning
confidence: 99%